Memprediksi Perkembangan Pendapatan pada Koperasi KW Dengan Metode Tren - Hadi Gustara; Irawan Irawan; Evi yuniarti (Politeknik Negeri Lampung, 2021)
This study aims to determine and predict the development of cooperative income and determine the trend method that has a relatively small risk of error to be used in analyzing and comparing the income prediction with the actual data. The type of data used is secondary data. The data collection method used is the documentation method. The documentation collected is in the form of monthly cooperative income reports from January to December 2019. The data analysis method used is quantitative and qualitative methods. The results of the discussion of this final project show that in the period January to December 2019 cooperative income has increased and decreased. The percentage of total increase and decrease in income from savings and loan services is more stable than the percentage of income from the procurement of goods and services which is volatile. The trend method which has a small risk of error in analyzing savings and loan service income is the quadratic method, while the exponential method is used for income from the procurement of goods and services